DEVELOPMENT OF A COMPUTATIONAL CODE FOR THERMODYNAMIC ANALYSIS OF ANGRA 2 AND 3 NUCLEAR POWER PLANTS - Anjos Maia de Souza, Tailana; Matos Ribeiro de Lima, Leon; Carvalho da Silva, Gabriely; Jian, Su (Revista de Engenharia Térmica, 2024)
With the 4th Industrial Revolution, many industry sectors are incorporating digital features, such as Internet of Things, Artificial Intelligence, Digital Twin, among others. In this context, the nuclear energy industry also demands for computational tools able to deal with design and operating data. This paper presents a thermodynamic analysis model for Angra 2 and 3 Nuclear Power Plants. It describes the development of a computational code that provides process data – temperature, pressure and mass flow rate – under steady state regimes. The basic mathematical models for the power plants processes are presented. The model covers the whole power generation process, including the primary circuit, which is composed by the reactor and cold and hot legs, the secondary cycle, which is the most complex one and consists on a regenerative Rankine power cycle, and the tertiary cycle, which is the sea water inlet and outlet. Results are shown for validation cases, by comparisons with heat balance diagrams of Angra 2 NPP for three different cases: (i) normal operation at 100% power load, (ii) normal operation at partial power load and (iii) preheating train bypass.